A highly sensitive fluorescence assay for 2, 4, 6-trinitrotoluene using amine-capped silicon quantum dots as a probe. Issue 5 (20th January 2015) - Ban, Rui; Zheng, Fenfen; Zhang, Jianrong
Abstract : A simple and effective fluorescence method for the detection of TNT has been developed based on the recognition of amine-capped silicon quantum dots (SiQDs) to TNT. Abstract : We present a simple and effective fluorescence method for the detection of 2, 4, 6-trinitrotoluene (TNT), which is based on TNT recognition by amine-capped silicon quantum dots (SiQDs). The highly luminescent functionalized SiQDs were obtained by a one-step hydrothermal process, using 3-aminopropyltrimethoxysilane as the precursor. The as-prepared SiQDs were directly used as a recognition probe for the detection of TNT because of the strong interactions between the TNT molecule and the SiQDs with an amine group. The formation of Meisenheimer complexes (TNT–amine complexes) could quench the fluorescence of SiQDs by fluorescence resonance energy transfer. Such fluorescence response could be used to quantify TNT over the range of 5–500 nM with a detection limit down to 1 nM, and has been successfully applied for the assay of TNT in spiked tap water. The probe exhibited excellent selectivity. This method has great potential for applications in TNT detection.